Gauging the Effects of Social Accountability on Services, Governance, and Citizen Empowerment. (10th June 2015) - Brinkerhoff, Derick W.; Wetterberg, Anna
Abstract: Engaging citizens in holding public officials and service providers accountable, referred to as social accountability, is a popular remedy for public sector performance weaknesses, figuring prominently in many international donor‐funded projects and leading to widespread replication. However, the contextual factors that influence the successful transfer of social accountability are debated. Demand‐side factors (civil society and citizens) are overemphasized in much of the literature. Yet supply‐side factors (state structures and processes) and the nature of state–society relations are also important. This article examines four projects in developing countries to explore how these contextual factors influenced social accountability aims and outcomes. The salience of supply factors in enabling social accountability for service delivery and government performance stands out, particularly the degree of decentralization and the availability of space for citizen engagement. The capacity and motivation of citizens to occupy the available space, aggregate and voice their concerns, and participate with state actors in assessing service delivery performance and problems are critical . Abstract : Brinkerhoff and Wetterberg Podcast Episode